Staggered Grid Computation of Fluid Flow with an Improved Discretisation of Finite Differencing - Nursalasawati, Binti Rusli; Ahmad Kueh, Beng Hong; Erwan Hafizi, Bin Kasiman (2011)
The present paper models the fundamental problems of fluid flow using a discretely improved finite difference method on a staggered computational grid. The developed finite difference formulation is applied to well-established benchmark problems, namely, the lid-driven cavity flow, the developing laminar flow in a straight rectangular duct and the backward-facing step flow. Excellent agreements have been found for all cases. Also, this approach has successfully handled the pressure of the flow that has been long considered as one of the main problems in using the finite difference method.